Ultra-compact Microstrip UWB bandpass filter with improved performance - Sahu B.; Singh S.; Meshram M.K.; Singh S.P. (My University, 2025)
In this paper, an ultra-compact Ultra-wideband (UWB) bandpass filter (BPF) based on modified multimode resonator (MMR) is proposed. The compactness of the proposed UWB BPF with good impedance matching in passband is achieved using modified MMR, which consists of meandered coupled lines, stepped-impedance stubs, open-circuited stubs and coupled-line sections. Stepped-impedance stubs which are used to nullify the effect of mutual coupling due to the presence of meandered coupled lines are analyzed in detail. The proposed filter is fabricated using Roger RT/duroid 5880 substrate (r = 2.2, thickness = 0.787 mm) having size of 14 mm × 5.9 mm. The experimental results show that the proposed filter has passband frequency range 3.05-10.9 GHz with upper wide stopband attenuation better than 38 dB up to 15.5 GHz. The simulation results are nearly in agreement with corresponding experimental results. © 2017 IEEE.